Early Effect of Bariatric Surgery on Urogenital Function in Morbidly Obese Men. Issue 2 (10th January 2017) - Aleid, Maha; Muneer, Asif; Renshaw, Sara; George, Jason; Jenkinson, Andrew D.; Adamo, Marco; Elkalaawy, Mohamed; Batterham, Rachel L.; Ralph, David J.; Hashemi, Majid; Cellek, Selim
Abstract: Introduction: Obesity is an independent risk factor for erectile dysfunction (ED) and lower urinary tract symptoms (LUTS). Bariatric surgery has been shown to improve erectile function and urinary symptoms in medium- to long-term studies (3- to 12-month postoperative follow-up). Aim: To investigate the early effect (1 month postoperatively) of bariatric surgery on ED and LUTS, which has not previously been investigated. Methods: Morbidly obese men (body mass index > 35 kg/m 2 ) undergoing bariatric surgery were asked to complete the International Index of Erectile Function (IIEF) and International Prostate Symptom Score (IPSS) questionnaires before surgery and 1, 3, and 6 months after surgery. Main Outcome Measure: The influence of bariatric surgery on urogenital function, body mass index, fasting blood glucose, and glycated hemoglobin were analyzed using parametric and non-parametric tests for paired samples. Results: Of 30 patients who completed the study, 18 reported ED (IIEF score < 25) and 14 reported moderate or severe LUTS (IPSS ≥ 8) before the operation. Twelve patients had ED and moderate or severe LUTS. IIEF score, IPSS, body mass index, percentage of weight loss, fasting blood glucose, and glycated hemoglobin showed significant and rapid improvement after bariatric surgery starting at the 1-month postoperative time point and improvement continued throughout the study in all patients with ED or moderate to severe LUTS. Conclusion: This is the first study showing improvement in erectile and urinary function within 1 month after bariatric surgery, an effect that was parallel to glycemic improvement and weight loss.